COMPARATIVE LEGAL REASONING AMONG ISLAMIC SCHOOLS OF THOUGHT: METHODS OF RESOLVING TA‘ĀRUḌ AL-ADILLAH (CONFLICTING EVIDENCES) - Muhammad Rizal Khoirul Umam; Mutho`, Izzul; Rozak , Abdul (LPPM STAI Muhammadiyah Probolinggo, 2025)
The phenomenon of conflicting legal evidences (ta‘āruḍ al-adillah) is a critical issue in the discipline of uṣūl al-fiqh, particularly in the process of Islamic legal reasoning (istinbāṭ al-ḥukm). This occurs when two or more legal texts appear to contradict each other in determining a legal ruling. Various Islamic legal schools developed distinct methods to resolve such conflicts. This study aims to conduct a comparative analysis of conflict-resolution methods in four major Sunni schools: Ḥanafī, Mālikī, Shāfi‘ī, and Ḥanbalī. It employs a qualitative research method with a normative-conceptual approach, relying on classical and contemporary literature in uṣūl al-fiqh. The findings reveal that although the schools differ in emphasis and procedural order—such as using tarjīḥ (preference), nasakh (abrogation), or al-jam‘ wa al-tawfīq (reconciliation)—they all uphold the integrity and authority of the legal texts. This study asserts that such methodological diversity should not be seen as contradiction, but as a reflection of the intellectual richness and flexibility inherent in Islamic law in addressing the complexities of social reality.